2012
DOI: 10.1590/s2179-975x2012005000006
|View full text |Cite
|
Sign up to set email alerts
|

Density and body size of the larval stages of the invasive golden mussel (Limnoperna fortunei) in two neotropical rivers

Abstract: AIM: The present study involved an analysis of the monthly variations in the population densities and body sizes of the different stages of planktonic larvae of the invasive golden mussel (Limnoperna fortunei), in the rivers Paraguay and Miranda; METHODS: The study was carried out between February 2004 and January 2005. Monthly collection of the plankton samples was accompanied by physical, chemical and biological analyses of the water; RESULTS: The Miranda River presented higher values of calcium, pH, alkalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
2
12
1
1
Order By: Relevance
“…Although the dimensionality of dissolved oxygen and larval stages of L. fortunei were located in opposite quadrants in the RDA, the mean values of oxygen were considerably high, with a minimum of 7 mg.l -1 in February. Despite Eilers et al (2011) observed a decrease in the larval density of L. fortunei during periods of lower dissolved oxygen concentration, our results did not present such pattern, since the month with the lowest values of dissolved oxygen (February) had higher peaks of larval density (16,000 ind.m -3 ). February was the most populous month of our whole sample period.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although the dimensionality of dissolved oxygen and larval stages of L. fortunei were located in opposite quadrants in the RDA, the mean values of oxygen were considerably high, with a minimum of 7 mg.l -1 in February. Despite Eilers et al (2011) observed a decrease in the larval density of L. fortunei during periods of lower dissolved oxygen concentration, our results did not present such pattern, since the month with the lowest values of dissolved oxygen (February) had higher peaks of larval density (16,000 ind.m -3 ). February was the most populous month of our whole sample period.…”
Section: Discussioncontrasting
confidence: 99%
“…The dominance of smaller larval stages at plankton (D-Shaped larvae and Straight Hinged) compared to larger ones, suggest that the last stages (Umbonated, Plantigrade and Pediveliger) have already tried some settlements on the substrates or they were naturally lost. Eilers et al (2011) when studying larval densities of L. fortunei in the Miranda and Paraguay Rivers also found higher densities of the initial stage (D-Shaped larvae), with a great population decrease together with the larvae maturing, with a reduction of ~80% of D-shaped larvae and ~10% of Umbonated.…”
Section: Discussionmentioning
confidence: 83%
“…Abundance cycles of L. fortunei larvae in the water column indicate that the mussel has an extended (7–10 months) reproductive period spanning from spring to autumn, and a single relaxation phase centred on the winter. This pattern is characteristic of all the sites surveyed in Argentina (Cataldo & Boltovskoy, ; Rojas Molina & José de Paggi, ; Boltovskoy et al ., ) and elsewhere, including Brazil (Eilers et al ., ) and Japan (Nakano et al ., ), with the sole exception of Salto Grande reservoir. Here, in addition to the winter drop, there was a very marked decline in January–April.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al (2005), from observations performed in Rio Grande do Sul State, reported that the minimum size of larvae is around 80 µm. (Eilers et al, 2011), through a discriminant analysis considering the proportion of different larval stage in samples collected in the Paraguay River, found that the stage "D" prevailed in 80% of the plankton larvae.…”
Section: Data Collection and Analysismentioning
confidence: 99%